Monoclonal Antibody‐Guided Tumor‐Targeted Hollow Virus‐Like Cerium Oxide with Oxygen Self‐Supply for Intensifying Photodynamic Therapy. Issue 8 (12th December 2022) - Li, Mengqi; Liu, Jiajing; Luo, Xian; Zhao, Zhiyu; Wang, Shengyu; Liu, Zongjunlin; Li, Tingting; Yang, Dong; Li, Yang; Wang, Peiyuan; Luo, Fanghong; Yan, Jianghua
Abstract: The hypoxic character of tumors and the poor targeting ability of photosensitizers often limit the efficacy of photodynamic therapy (PDT). In recent years, the discovery of metal nanoenzymes and nanocarriers has improved PDT. Thereby, to improve the effective utilization of photosensitizers and oxygen (O2 ) in tumors, herein, a nanosystem (LS‐HB@HvCeO2 ‐NRP1 mAb, LHCN1) is reported, in which a hollow virus‐like cerium oxide (HvCeO2 ) is surface‐decorated with tumor‐targeting neuropilin‐1 monoclonal antibody (NRP1 mAb), and loaded with a photosensitizer (chlorin e6‐C‐15‐ethyl ester, LS‐HB). In vitro and in vivo experiments demonstrate that LHCN1 can efficiently accumulate within the tumor sites via the targeting guidance of NRP1 mAb and is then rapidly endocytosed into cells. Furthermore, HvCeO2 with catalase‐mimetic activity can decompose the endogenous hydrogen peroxide (H2 O2 ) to promote O2 via the valence transformation between Ce 4+ and Ce 3+, relieving tumor hypoxia and improving the PDT efficacy. Upon near‐infrared laser irradiation, LS‐HB produces large amounts of cytotoxic reactive oxygen species. Moreover, LHCN1 is used in fluorescence/photoacoustic multimodal imaging for in vivo drug localization, and its use in PDT evidently helps inhibit tumor growth with no apparent toxicity to normal tissues. Thus, LHCN1 may provide a promising strategy for precise tumor‐specific diagnosis and treatment. Abstract : The neuropilin‐1 monoclonal antibody (NRP1 mAb) of LS‐HB@HvCeO2‐NRP1 mAb (LHCN1) nanoparticle specifically targets the tumor and binds neuropilin‐1 (NRP1) on the cytomembrane. After NRP1 mediates the nanoparticles internalization into cytoplasm, CeO2 of LHCN1 decomposes the endogenous H2O2 to produce O2 for photodynamic therapy of LS‐HB. Under 660 nm laser irradiation, LS‐HB generates amounts of 1 O2 to kill tumor cells.